Exploring lithium extraction technologies in oil and gas field-produced waters: from waste to valuable resource - K. Karuppasamy; Ahmad Mayyas; Emad Alhseinat; Haitem Hassan-Beck; Akram Alfantazi (Chemical Engineering Journal Advances)
The massive development of electric vehicles and consumer electronic industries has recently escalated the demand for lithium supply and price worldwide. Since lithium is the prime source compound for lithium-ion batteries in electronic sectors, its scarcity in nature becomes worrisome and urges the scientific community to find alternate resources for lithium. The undesired product obtained from oil and gas industries, i.e., oil and gas field-produced water (OGPW), is a promising resource for effectively extracting lithium. Nevertheless, most of the reported methodologies for lithium extraction from OGPW are still in their early stages and have not yet been commercialized. This review explores the recent advancements, practical difficulties, and forthcoming prospects for extracting lithium from OGPW utilizing diverse technologies. An overview of the crucial challenges of several recovery methods, including technology and costs, has been discussed. Hybrid technology combining pretreatment, concentration, and enrichment processes for improved lithium recovery performance has been elaborated in detail and offers the idea of filling the gap between the demand and supply for lithium.